Lifestyle of a Roman Imperial community: ethnobotanical evidence from dental calculus of the Ager Curensis inhabitants - Alessia D'Agostino; Angelo Gismondi; Gabriele Di Marco; Mauro Lo Castro; Rosaria Olevano; Tiziano Cinti; Donatella Leonardi; Antonella Canini (BMC, 2019)
Abstract Background The analysis of ancient calcified dental plaque is a powerful archaeobotanical method to elucidate the key role of the plants in human history. Methods In this research, by applying both optic microscopy and gas chromatography mass spectrometry on this matrix, a detailed qualitative investigation for reconstructing the lifestyle of a Roman imperial community of the Ager Curensis (Sabina Tiberina, Central Italy) was performed. Results The detection of animal micro-remains and molecules (e.g., hairs, feather barbules, markers of dairy products), starch granules of several cereals and legumes, pollen (e.g., Juglans regia L., Hedera sp. L.) and other plant micro-debris (e.g., trichome of Olea sp., hemp fibers), and phytochemicals (e.g., Brassicaceae, Lamiaceae herbs, Ferula sp., Trigonella foenum-graecum L., wine, and Humulus lupulus L.) in the dental calculus sample demonstrated that plant-derived foods were regularly consumed together with animal resources. Conclusions This nutritional plan, consistent with the information reported in ancient written texts, suggested that the studied population based its own subsistence on both agriculture and husbandry, probably also including beekeeping and hunting activities. All together, these results represent proofs for the comprehension of food habits, phytotherapeutic practices, and cultural traditions of one of the first Roman settlements in the Sabina Tiberina area.